Winkler, Riley County - Winkler, Brendan (Kansas State University, The Chapman Center for Rural Studies, 2010)
The decay of Winkler was the loss of not having a railroad run through the town site. A railroad running through a town almost guarantees growth and survival for small towns in Kansas. Glen Stockwell, a local resident near Winkler during the 1930s, remembered that originally the Leavenworth-Kansas-Western railroad planned on running a line up Fancy Creek, through Winkler. However, the plan fell apart and the line was sent down to Garrison, then to Leonardville.
Brendan Winkler, “Winkler, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/54.
Keywords: Blue River Valley; Fancy Creek River Valley; Gebhardt Family; Riley County; St. Johns Lutheran Church; Winkler Mill